THE INFLUENCE OF INQUIRY LEARNING METHOD AND SELF-RELIANCE LEARNING ON IPS OUTCOMES IN FOURTH GRADE AT SD NEGERI 060874 - Eka Putri Kartini Pasaribu; Samsidar Tanjung; Edidon Hutasuhut (Jurnal Ilmiah Teunuleh, 2021)
This study aims to find out the use of inquiry learning models and conventional learning models in student IPS learning outcomes, to know the differences in IPS learning outcomes of students who have high learning independence with students who have low learning independence, and to know the interaction between the learning model and the independence of learning to the student's IPS learning outcomes. This research is a quasi-experimental study with the research population is all grade IV students as many as 60 students with samples are all grade IV students (A and B) who take IPS subjects. From the research, it was produced that the inquiry learning model is higher than the use of conventional learning model shown by Fcount = 3.86 > Ftable = 2.77 at a significant level a= 0.05. IPS learning outcomes of students who have higher learning independence than students who have low learning independence indicated by Fcount = 3.74 > Ftable = 2.77 at a significant level a= 0.05. There is an interaction between the learning model and the independence of learning to the student's IPS learning outcomes indicated by Fcount = 3.64 > Ftable = 2.77 at a significant level a= 0.05. The conclusion of this study shows that inquiry learning is better used for students who have high learning independence while conventional learning models are well used for students who have low learning independence in order to have interactions between learning models and self-reliance learning.